Concerning the Program of Understanding a Literary Text - Gasparyan, Seda (Armenian Folia Anglistika, 2018)
Text is a broad notion. It may be expressed both in writing and orally in the form of a monologue, dialogue, utterance, etc. This may well be the reason for the persistent interest towards text as such. The great variety of studies on the nature of text and its objectives, however, are all somewhat controversial and lack a unified conceptual approach. Things get even more complicated due to the fact that now into scientific circulation has been introduced the notion of discourse, and evidently of considerable popularity in the current stage of the development of linguistics is the relationship between text and discourse. The present article focuses on the study of the correlation of text and discourse, views literary text as a unit of specific communication between the writer and the reader, as well as centers the attention on the consecutive stages of literary text perception and understanding.